Investigating the Methodology Used by Libyan Teachers in Teaching Speaking Lessons for Secondary Students: A Study at Om_Salama Secondary School in Misurata Libya 2018/2019 - Mohsen, Al Hussein Saleem; Alsanousi, Zainab Ali (جامعة المرقب - كلية التربية بالخمس, 2020)
تعمل هذه الورقة البحثية على دراسة المنهجية المستخدمة من قبل المعلمين الليبيين في تدريس مهارة التحدث باللغة الإنجليزية والأسباب الكامنة وراء تردد الطلاب في التحدث بها. وهي تدرس، أيضا، أسباب عدم رغبة الطلاب في استخدام اللغة الإنجليزية كوسيلة للتفاعل داخل الفصل وتقترح بعض الحلول التي قد تساعدهم في التحدث باستخدامها. تم استخدم وسيلة الملاحظة لجمع بيانات ومعلومات البحث الذي استهدف طلاب مدرسة أم سلمة الثانوية بمدينة مصراته (الليبية) وتحديدا طلاب السنة الثانية والثالثة. كما تم إعطاء نموذج استبيان لعدد 12 طالبا من الطلاب الذين أجريت عليهم الملاحظة وذلك للعثور على العقبات التي يواجهها الطلاب خلال تعلم التحدث باللغة الإنجليزية. تظهر النتائج أن الطلاب على وعي تام بأهمية إتقان مهارة التحدث والتفاعل في الفصل باستخدام اللغة الإنجليزية، لكن معظم المعلمين لا يمنحونهم الفرص والأنشطة التي تساعدهم، بدورها، في التحدث والتفاعل مع زملائهم في الفصل.
This paper investigates the methodology used by Libyan teachers in teaching speaking to secondary school students and the reasons behind students’ reluctance to speak the language in classrooms. This paper studies the causes for students’ unwillingness to use English in interaction and suggests some solutions that might help them speak. An observation of the teaching and learning practices took place in Om_Salama Secondary School in the city of Misurata in Libya where the students of the second and third year and their teachers were participants of the study. A questionnaire was administered to 12 students in order to find the obstacles that they face in their learning process. The findings show that students are aware of the importance of speaking skill and the interaction in class; however, most teachers do not give them the opportunity to speak or the suitable speaking activities and techniques that help them use the language.
Keywords: طرق التدريس -- تدريس اللغة الإنجليزية -- التعليم الثانوي -- ليبيا